2020
DOI: 10.14421/biomedich.2020.92.65-75
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Content and Antimicrobial, Antioxidant and Hemolytic Activities of Essential Oils from Four Selected Medicinal Plants Growing in Algeria

Abstract: The Saharan and steppe spontaneous plants are very characteristic because of their particular adaptation to the desert and extreme environment. Some species have pharmacological properties that give them a medicinal interest. The aim of the present work was to determine the polyphenol contents of essential oils obtained from four endemic plants growing in Algeria (Pituranthos scoparius, Myrtus nivellei, Rosmarinus officinalis and Mentha piperita), and study its biological activity, including antimicrobial, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These results can be compared to a study, conducted by Krishna et al [ 44 ], where a Mulberry fruit polyphenolic extract exhibited a hemolysis percentage of 53.98 ± 0.06 when 100 µg/mL were used. Another study, conducted by Halla et al [ 45 ], showed that the essential oils of some medicinal plants from Algeria, such as Pituranthos scoparius , Myrtus nivelllei , Rosmarinus officinalis , and Mentha piperita , show 93.00, 72.88, 72.75, and 43.26% of hemolytic activity, respectively, when using a concentration of 3.12 mg/mL. This was achieved after incubating the extract with the red cells for 120 min at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results can be compared to a study, conducted by Krishna et al [ 44 ], where a Mulberry fruit polyphenolic extract exhibited a hemolysis percentage of 53.98 ± 0.06 when 100 µg/mL were used. Another study, conducted by Halla et al [ 45 ], showed that the essential oils of some medicinal plants from Algeria, such as Pituranthos scoparius , Myrtus nivelllei , Rosmarinus officinalis , and Mentha piperita , show 93.00, 72.88, 72.75, and 43.26% of hemolytic activity, respectively, when using a concentration of 3.12 mg/mL. This was achieved after incubating the extract with the red cells for 120 min at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
“…These results can be compared to a study, conducted by Krishna et al [44], where a Mulberry fruit polyphenolic extract exhibited a hemolysis percentage of 53.98 ± 0.06 when 100 µg/mL were used. Another study, conducted by Halla et al [45], showed that the essential oils of some medicinal plants from Algeria, such as Pituranthos scoparius, Myrtus nivelllei, Rosmarinus officinalis, and Mentha piperita, show 93.00, 72.88, 72.75, and 43.26% of hemolytic activity, respectively, when using a concentration of 3.12 mg/mL. This was achieved after incubating the extract with the red cells for 120 min at 37 • C. The fact that the Mexican rambutan peel extracts exhibited no hemolysis is a promising result that can be related to the high amount of hydrolyzable polyphenols with a high antioxidant activity, which allows them to have protective effects against oxidative damage and keep the membrane of red blood cells intact [46].…”
Section: Hemolytic Activitymentioning
confidence: 99%